PENGARUH PRENATAL YOGA TERHADAP PENURUNAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER II DAN III - Bunda, Rahmatiar (Journal of Midwifery Tiara Bunda, 2024)
Background: In Indonesia, it was reported that the prevalence of back pain in pregnant women in the third trimester was 70% of pregnant women experiencing back pain in the third. The aim of this research is to determine the effect of prenatal yoga on reducing back pain in pregnant women. Method used in this research is a True Experiment research design using a Posttest Only Control Design, that is, this design does not carry out a pretest on the subjects. Research results: The level of back pain before doing prenatal yoga was 1-3 (mild pain) for 4 respondents (27%), 4-6 (moderate pain) for 11 respondents (73%) and 7-10 (severe pain) for 0 respondents. (0%). And after doing prenatal yoga 1-3 (mild pain) 15 respondents (100%), 4-6 (moderate pain) 0 respondents (0%) and 7-10 (severe pain) 0 respondents (0%). Data analysis using the Shapiro Wilk Normality Test was obtained with a significant value of 0.00 < α = 0.05, indicating that there is an influence of prenatal yoga on back pain in pregnant women.